2020
DOI: 10.1111/cea.13787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adherence to corticosteroids in asthma by drug monitoring or fractional exhaled nitric oxide: A literature review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In addition, the comparison with other objective measures of inhaler adherence, such as pharmacy refill data, was not possible. Nevertheless, we need to consider that currently available objective methods require laborious analysis by physicians, are costly to implement in clinical practice and, like inhaled corticosteroid serum level and FeNO suppression test, 53 , 54 are not fully validated. Another important limitation is that patient and physician adherence data was retrieved at a different time point than that of the application, therefore a future improvement would be tracking all measurements at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the comparison with other objective measures of inhaler adherence, such as pharmacy refill data, was not possible. Nevertheless, we need to consider that currently available objective methods require laborious analysis by physicians, are costly to implement in clinical practice and, like inhaled corticosteroid serum level and FeNO suppression test, 53 , 54 are not fully validated. Another important limitation is that patient and physician adherence data was retrieved at a different time point than that of the application, therefore a future improvement would be tracking all measurements at the same time points.…”
Section: Discussionmentioning
confidence: 99%
“…This has obvious clinical utility as it can quickly identify those patients who are unlikely to achieve control of type-2 inflammation using inhaled treatment alone and could progress quickly to biologic therapy, but in parallel it can identify those patients where the clinical focus needs to be on better adherence with inhaled treatment. A recent systematic literature review [ 66 ] examining the assessment of adherence to corticosteroids in asthma by drug monitoring or F ENO supports this use of F ENO SuppT as well as outcome data from small single centre studies [ 67 , 68 ]. Additionally, this was further supported by the largest case series from the RASP-UK programme which demonstrated that a positive F ENO SuppT was associated with significantly fewer patients progressing to biologic therapy and a significantly greater chance of being discharged from hospital [ 69 ].…”
Section: Measuring and Identifying Non-adherencementioning
confidence: 96%
“…151,152 Assessment of nonadherence is difficult and a single gold standard measure does not exist but traditional measures have included FeNO monitoring and prednisolone assays. 153 Emerging tools include remote inhaler monitoring, remote FeNO suppression tests, using simplified dosing regimes where possible and use of interactive digital technologies. [154][155][156][157][158]…”
Section: Smokingmentioning
confidence: 99%